Interpersonal contacts and conflicts at the tourist agencies - Magdaléna Ďuričeková (Palacký University Olomouc, 2010)
The interpersonal contact with a client is of a great importance at the tourist agencies, because during the interaction comes to satisfying expectations of requirements of clients. It quite often happens that the low quality of goods and services is possible to compensate with the high quality of interpersonal contact and vice versa, even the good product can be unacceptable because of the low quality of service. The moment of delivering services always concerns at least two sides /people/. Therefore it should be looked at from two perspectives: the view of contact personnel, the workers who are in direct contact with the outer client and from the view of the client. Not even the greatest effort of the management of tourist agency can exclude the possibility of any conflict in case the contact workers do not know /they have not been trained properly/ or do not want to approach the clients accepting their personality and their requirements. Generalization from the practice records that the knowledge of possible conflicts and their reasons are very important for the success of any company.